2021
DOI: 10.1101/2021.01.20.425322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coupled myovascular expansion directs cardiac growth and regeneration

Abstract: Innate heart regeneration in zebrafish and neonatal mammals requires multiple cell types, such as epicardial cells, nerves, and macrophages, to enable proliferation of spared cardiomyocytes (CMs). How these cells interact to create growth niches is unclear. Here we profile proliferation kinetics of cardiac endothelial cells (CECs) and CMs in the neonatal mouse heart and find that CM and CEC expansion is spatiotemporally coupled. We show that coupled myovascular expansion during cardiac growth or regeneration i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…Along the same line of observations, stabilizing vessel-like structures in the non-regenerating medaka hearts after cardiac injury, significantly reduced scarring (Lai et al, 2017;Marín-Juez et al, 2019). Similarly, enhancing collateral formation in adult mouse hearts after MI results in a significant improvement in cardiac function (Das et al, 2019;Debenedittis et al, 2021). All of these data and observations emphasize the important role of coronary revascularization in promoting cardiac regeneration after cardiac injury.…”
Section: Coronariessupporting
confidence: 53%
See 4 more Smart Citations
“…Along the same line of observations, stabilizing vessel-like structures in the non-regenerating medaka hearts after cardiac injury, significantly reduced scarring (Lai et al, 2017;Marín-Juez et al, 2019). Similarly, enhancing collateral formation in adult mouse hearts after MI results in a significant improvement in cardiac function (Das et al, 2019;Debenedittis et al, 2021). All of these data and observations emphasize the important role of coronary revascularization in promoting cardiac regeneration after cardiac injury.…”
Section: Coronariessupporting
confidence: 53%
“…Indeed a recent study by Das and colleagues revealed that CXCR4 is a main player promoting the formation of these collaterals in the regenerating neonatal mouse heart, and that inducing collateral formation in the adult mouse heart resulted in a significant functional improvement following MI (Das et al, 2019). Moreover, it has been recently shown that improving coronary revascularization in the adult mouse heart, stimulates CM proliferation (Debenedittis et al, 2021). All of these data suggest that coronaries are a vital factor that contributes to the regenerative outcome following injury.…”
Section: Poor Revascularization Potential In the Adult Mammalian Heartmentioning
confidence: 99%
See 3 more Smart Citations